Can leaf traits related to photoacclimation help explain the disappearance of an endangered palm species in deforested landscapes? - Freitas Cerqueira, Amanda (2025)
Euterpe edulis is a palm species native to the Brazilian Atlantic Forest (AF), a tropical biome severely threatened by deforestation. Previous studies have demonstrated that young E. edulis are absent from forest fragments embedded in deforested landscapes, where elevated light transmission (T) is observed in the forest understory. Based on data collected from young E. edulis in fifteen forest fragments (natural shade) and eighteen shade houses (artificial shade), we investigated the influence of T on six leaf traits related to photoacclimation capacity. We addressed the following questions: (i) Do leaf traits responses to T differ between natural and artificial shade? (ii) Which leaf traits exhibit the greatest plasticity in response to T variation? (iii) Can variation in these traits help explain the absence of young E. edulis in forest fragments within deforested landscapes? We found more uniform leaf trait patterns under artificial shade compared to natural shade. Among all analyzed leaf traits, reduced values of leaf chlorophyll index (CI) and leaf density (LVD) under high T were associated with the absence of E. edulis in highly deforested landscapes. Furthermore, CI, LVD and leaf mass per area (LMA) exhibited the highest plasticity to T variation and and emerged as the most responsive traits for assessing the establishment and growth potential of E. edulis under natural or artificial shade. These findings suggest that these leaf traits are valuable functional indicators for monitoring population dynamics and guiding reintroduction and restoration efforts of this endangered palm species in fragmented tropical forest landscapes.